EVALUATING THE SCHOOL LITERACY MOVEMENT PROGRAM USING THE CIPP MODEL AT AL IZZAH INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN MAKASSAR - Muallim Muallim (Yayasan Amanah Nur Aman, 2026)
The low literacy skills of Indonesian students present a national education challenge, which the government has responded to through the School Literacy Movement (GLS). This study aims to evaluate the effectiveness of the GLS implementation at Al Izzah Integrated Islamic Elementary School in Makassar using the CIPP evaluation model (Context, Input, Process, Product). The research employs a qualitative case study method with data collection through observation, in-depth interviews, and documentation. The findings of the study are as follows: (1) Context: The program is highly relevant to the needs of students and the school’s vision; (2) Input: The readiness of resources is adequate, supported by innovative literacy facilities and integrated funding; (3) Process: The implementation is consistent with a 15-minute daily reading routine, although challenges such as the dominance of gadgets among students remain; (4) Product: The program effectively increases reading interest, fosters independent reading habits, and supports academic achievement. In conclusion, the GLS at Al Izzah Integrated Islamic Elementary School has been effective in creating a conducive literacy ecosystem. It is recommended to update the book collection and strengthen teacher mentoring to address student boredom